2013
DOI: 10.1111/pce.12146
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite analysis of the effects of elevated CO2 and nitrogen fertilization on the association between tall fescue (Schedonorus arundinaceus) and its fungal symbiont Neotyphodium coenophialum

Abstract: Atmospheric CO2 is expected to increase to between 550 ppm and 1000 ppm in the next century. CO2-induced changes in plant physiology can have ecosystem-wide implications and may alter plant-plant, plant-herbivore and plant-symbiont interactions. We examined the effects of three concentrations of CO2 (390, 800 and 1000 ppm) and two concentrations of nitrogen fertilizer (0.004 g N/week versus 0.2 g N/week) on the physiological response of Neotyphodium fungal endophyte-infected and uninfected tall fescue plants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 49 publications
(61 reference statements)
6
60
0
Order By: Relevance
“…Based on previous research, the fitness level of M. persicae was decreased when feeding on the pepper plants grown under higher CO 2 concentrations. Similar results were recorded on species of Brassicaceae (Oehme et al, 2011) such as Brevicoryne brassicae on Brussels sprout (Ryan et al, 2014), and Acyrthosiphon pisum on the broad bean (Ryan et al, 2014). Other than that, elevated CO 2 also affects their morphology and physiology by reducing fertility and producing a fewer number of offspring, as well as increasing chewing insects development duration (Dáder et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Based on previous research, the fitness level of M. persicae was decreased when feeding on the pepper plants grown under higher CO 2 concentrations. Similar results were recorded on species of Brassicaceae (Oehme et al, 2011) such as Brevicoryne brassicae on Brussels sprout (Ryan et al, 2014), and Acyrthosiphon pisum on the broad bean (Ryan et al, 2014). Other than that, elevated CO 2 also affects their morphology and physiology by reducing fertility and producing a fewer number of offspring, as well as increasing chewing insects development duration (Dáder et al, 2016).…”
Section: Discussionsupporting
confidence: 75%
“…Nutrient-induced changes in host-symbiont interactions have been well studied in terrestrial plant-fungal associations [68], but much less is known about it in aquatic systems. There are still large gaps in our understanding on how nutrients affect marine symbioses.…”
Section: Resultsmentioning
confidence: 99%
“…Regallo), elevated CO 2 (700 ppm) caused an increase in the accumulation of carbohydrates, and a decrease in AAs and total nitrogen (N) in leaves (Aranjuelo et al 2011). Similarly, in tall fescue (Schedonorus arundinaceus) treated with elevated and high CO 2 showed that both treatments increased the concentration of water-soluble carbohydrates compared to ambient controls (Ryan et al 2014). It is interesting to note that in the two aforementioned studies, decreases in AAs and total N-content were observed, thus indicating increases in C/N ratio due to elevated CO 2 .…”
Section: Introductionmentioning
confidence: 99%